2018
DOI: 10.1007/s00270-018-1972-6
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Embolization of Type II Congenital Extrahepatic Portosystemic Shunt with Hematochezia: A Case Series and Review of the Literature

Abstract: Hematochezia is a rare clinical presentation of congenital extrahepatic portosystemic shunt (CEPS). We describe a series of three patients with type II CEPS presenting as hematochezia that were treated by catheter embolization, followed by a brief review of published articles. Hematochezia of the patients was due to the giant inferior mesenteric vein, superior rectal vein and colonic varices. The catheter embolization was successfully accomplished in all of the patients. After a mean follow-up of 27 months, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In combination with other congenital malformations, patients with CEPS present with hypergalactosemia, high bile acid, high serum ammonia, and hepatic encephalopathy caused by the portal and vena cava shunt. It has been reported that 66-100% of the patients with CEPS have hyperammonemia and 17-30% have hepatic encephalopathy [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…In combination with other congenital malformations, patients with CEPS present with hypergalactosemia, high bile acid, high serum ammonia, and hepatic encephalopathy caused by the portal and vena cava shunt. It has been reported that 66-100% of the patients with CEPS have hyperammonemia and 17-30% have hepatic encephalopathy [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Angiography is the gold standard for diagnosing CEPS and identifying the type of CEPS present [ 8 , 9 ]. While shunt anatomy and flow dynamics can be determined by angiography and/or direct venography, balloon shunt occlusion venography is critical for detecting intrahepatic portal vein branches.…”
Section: Discussionmentioning
confidence: 99%
“…Portal vein and mesenteric venous thrombosis is a common complication after shunt ligation that can lead to portal hypertension; therefore, postprocedural anticoagulation therapy is very essential [ 4 , 8 ]. Heparin and warfarin have been used to prevent thrombosis in previous studies; however, the activated partial thromboplastin time and international normalized ratio should be closely monitored to adjust drug dosage [ 14 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the severity of complications and their potential reversibility after suppression of the shunts, closure or ligation of a shunt in type 2 CEPS is necessary [7]. It is performed either surgically or with percutaneous transcatheter embolization [20]. Various studies have strongly recommended that, when a shunt is detected with no clinically significant complications and is confirmed to be permanent, it should be closed before a significant complication occurs if a closure can be performed satisfactorily [821].…”
Section: Discussionmentioning
confidence: 99%